2006
DOI: 10.1101/gad.1412706
|View full text |Cite
|
Sign up to set email alerts
|

SirT2 is a histone deacetylase with preference for histone H4 Lys 16 during mitosis

Abstract: The mammalian cytoplasmic protein SirT2 is a member of the Sir2 family of NAD + -dependent protein deacetylases involved in caloric restriction-dependent life span extension. We found that SirT2 and its yeast counterpart Hst2 have a strong preference for histone H4K16Ac in their deacetylation activity in vitro and in vivo. We have pinpointed the decrease in global levels of H4K16Ac during the mammalian cell cycle to the G 2 /M transition that coincides with SirT2 localization on chromatin. Mouse embryonic fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
504
3
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 576 publications
(540 citation statements)
references
References 25 publications
27
504
3
6
Order By: Relevance
“…Although caloric restriction has been shown to activate SIRT2 in a nicotinamide adenine dinucleotide + -dependent manner, the regulatory mechanism for SIRT2 deacetylase activity is not fully understood. 16 This study showed that angiotensin II-angiotensin II type 1 receptor-induced tubulin deacetylation is mediated by SIRT2, suggesting that angiotensin II type 1 receptor signaling is a novel SIRT2 deacetylase regulator. In this study, SIRT2 expression was not changed by angiotensin II in EA hy.926 cells (data not shown).…”
Section: Sirt2 and Endothelial Microtubule Reorganization A Hashimotomentioning
confidence: 75%
“…Although caloric restriction has been shown to activate SIRT2 in a nicotinamide adenine dinucleotide + -dependent manner, the regulatory mechanism for SIRT2 deacetylase activity is not fully understood. 16 This study showed that angiotensin II-angiotensin II type 1 receptor-induced tubulin deacetylation is mediated by SIRT2, suggesting that angiotensin II type 1 receptor signaling is a novel SIRT2 deacetylase regulator. In this study, SIRT2 expression was not changed by angiotensin II in EA hy.926 cells (data not shown).…”
Section: Sirt2 and Endothelial Microtubule Reorganization A Hashimotomentioning
confidence: 75%
“…For example, histone H4K16 and α‐tubulin‐K40 have been indicated as the potential targets of Sirt2 to modulate chromatin conformation and microtubule stability (North et al., 2003; Vaquero et al., 2006). Sirt2 participates in myelin formation of Schwann cells by deacetylating partitioning defective 3 homologue (PAR3) (Beirowski et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the nucleus, SIRT2 deacetylates H4-K16, and during the G2/M transition, global levels of H4-K16 acetylation decrease, which may aid in chromatin condensation (Vaquero et al, 2006). As overexpression of SIRT2 delays mitotic exit, SIRT2 might function as a mitotic checkpoint protein by preventing chromatin condensation in response to mitotic stress (Dryden et al, 2003;Inoue et al, 2006).…”
Section: Regulation Of a Mitotic Checkpoint By Sirt2mentioning
confidence: 99%